2021
DOI: 10.1016/j.molliq.2021.116537
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the new COVID-19 target neuropilin-1 in complex with SARS-CoV-2 S1 C-end rule peptide and small-molecule antagonists

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the current coronavirus 2019 (COVID-19) pandemic, uses its spike (S1) protein for host cell attachment and entry. Apart from angiotensin-converting enzyme 2, neuropilin-1 (NRP1) has been recently found to serve as another host factor for SARS-CoV-2 infection; thus, blocking S1–NRP1 interaction can be a potential treatment for COVID-19. Herein, molecular recognition between SARS-CoV-2 S1 C-end rule (CendR) heptapeptide including small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The results obtained in this study suggest that the lower severity of SARS-CoV-2 infection observed in children may be due to a different expression in the respiratory tract of NRP1, the pivotal co-receptor that enhance SARS-CoV-2 entry into the host cells (17,18). This data also support the potential role of NRP1 as therapeutic target against COVID-19, as suggested by others (33).…”
Section: Discussionsupporting
confidence: 86%
“…The results obtained in this study suggest that the lower severity of SARS-CoV-2 infection observed in children may be due to a different expression in the respiratory tract of NRP1, the pivotal co-receptor that enhance SARS-CoV-2 entry into the host cells (17,18). This data also support the potential role of NRP1 as therapeutic target against COVID-19, as suggested by others (33).…”
Section: Discussionsupporting
confidence: 86%
“…A novel study observed a significant reduction of cell infection following pre-incubation of SARS-CoV-2 pseudovirus with recombinant soluble extracellular b1b2 domain of NRP-1 ( Cantuti-Castelvetri et al, 2020 ). Several amino acid residues at the NRP-1 binding site (Y297, W301, N313, T316, P317, E319, D320, S346, E348, T349, K351, and Y353) have become a target of interest to block SARS-CoV-2 S1 interaction ( Klaewkla et al, 2021 ; Charoute et al, 2022 ). Two monoclonal antibodies and a known NRP-1 antagonist molecule, EG00229, exhibited a considerable decrease in SARS-CoV-2 infection in cell culture by disrupting the interaction between the spike protein and the b1 domain of NRP-1 through high specificity binding of the NRP-1 CendR motif ( Daly et al, 2020 ).…”
Section: Neuropilin-1 For Therapeutic Interventions In Sars-cov-2 Inf...mentioning
confidence: 99%
“…Two monoclonal antibodies and a known NRP-1 antagonist molecule, EG00229, exhibited a considerable decrease in SARS-CoV-2 infection in cell culture by disrupting the interaction between the spike protein and the b1 domain of NRP-1 through high specificity binding of the NRP-1 CendR motif ( Daly et al, 2020 ). Later comparisons highlighted that EG0137, R683G and A684M showed a greater affinity for the NRP-1 CendR binding region possibly due to interactions with more amino acid residues than EG00229 ( Klaewkla et al, 2021 ). Furthermore, the R683G and A684M peptides also displayed a higher NRP-1 binding efficiency than the SARS-CoV-2 S1 CendR heptapeptide ( Klaewkla et al, 2021 ).…”
Section: Neuropilin-1 For Therapeutic Interventions In Sars-cov-2 Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although the interaction with Asp320 was considered crucial for the binding, some studies suggested that a good affinity can also be achieved with antagonists lacking this interaction [40,42], expanding the possibilities for future structural modifications of small-molecule NRP1 antagonists. However, this interaction has still been recognised as critical for the SARS-CoV-2 binding [46], thus targeting it aims at successfully disrupting the SARS-CoV-2 NRP1 binding and is considered an attractive therapeutic approach to prevent viral entry. The well-known peptidomimetic NRP1 antagonist EG00229 (Figure 2A), which binds to the CendR-binding pocket and prevents the VEGF-A binding, was also evaluated for blocking the spike CendR binding in two different assays.…”
Section: Introductionmentioning
confidence: 99%